Fibrotic Scar After Spinal Cord Injury: Crosstalk With Other Cells, Cellular Origin, Function, and Mechanism - Li, Ziyu; Yu, Shuisheng; Hu, Xuyang; Li, Yiteng; You, Xingyu; Tian, Dasheng; Cheng, Li; Zheng, Meige; Jing, Juehua (Frontiers in Cellular Neuroscience, 2021)
The failure of axonal regeneration after spinal cord injury (SCI) results in permanent loss of sensorimotor function. The persistent presence of scar tissue, mainly fibrotic scar and astrocytic scar, is a critical cause of axonal regeneration failure and is widely accepted as a treatment target for SCI. Astrocytic scar has been widely investigated, while fibrotic scar has received less attention. Here, we review recent advances in fibrotic scar formation and its crosstalk with other main cellular components in the injured core after SCI, as well as its cellular origin, function, and mechanism. This study is expected to provide an important basis and novel insights into fibrotic scar as a treatment target for SCI.